Estudio cualitativo sobre la implementación del Programa de continuidad de cuidados y rehabilitación para personas con trastornos mentales graves en el Perú - Diez-Canseco, Francisco (Rev Panam Salud Publica, 2020)
OBJECTIVE. Describe the implementation of the Continuity of Care and Rehabilitation Program (PCC-R) in community mental health centers (CSMCs, Spanish acronym) in Peru. METHODS. Qualitative study of the implementation of the PCC-R in four CSMCs in Lima and La Libertad, Peru. Forty-two individual semi-structured interviews were conducted, as well as a focus group with five participants, for a total of 47 informants, including users, family members, and professionals involved in the design, implementation, and monitoring of the program. RESULTS. The PCC-R is a key program for community mental health services in Peru and it enjoys broad acceptability. Providers and users report satisfaction with its results; however, the program lacks a policy document specifying its objectives, organization, and activities. This would explain the variability in its implementation. The PCC-R has limitations in terms of management of financial and human resources, and it is necessary to improve training and supervision. There is consensus on the need, usefulness, and viability of developing a system to monitor the PCC-R. Good practices and suggestions are presented with a view to addressing these challenges. CONCLUSIONS. The PCC-R is a flagship program for the CSMCs and for the mental health reform in Peru. It has achieved broad acceptability among providers and users. Its implementation combines successes and difficulties, with pending tasks that include developing a policy document, improving resource management, strengthening training and supervision, and implementing a monitoring system for continuous improvement of the program.